Our heart fills with pride: expression of emotions in José Martí's oratory (Islas, 2022)
ABSTRACT: Introduction: This research responds to the necessity to delve into the ways used by José Martí to convince his audience powerfully, at a crucial moment in our history. Based on the criterion that in enunciation, discursive images are constructed, attempts are made to determine the form and function of the idiomatic signs that construct the image of the enunciator in the emotive dimension. Methods: To this end, a methodology has been developed with a pragmatic approach, which reconciles essential issues of discourse analysis, semantics and enunciation theory. Results: Four fundamental ways of constructing the image of the enunciator are identified, as well as the presence of varied grammatical resources through which the overflow is manifested in Martí's oratory. The results reveal how the speaker relies on the semantic-pragmatic properties of the structures identified as a resource for persuasion. Conclusions: The structures that construct the image of the enunciator in the emotive dimension have a metacommunicative, self-referential, pragmatic function, which is aimed at guaranteeing the adequate conditions of communication.
Keywords: image; enunciation; sentence; enunciator; emotive dimension